Analisis Daya Tarik Dan Kualitas Pengelolaan Usaha Retail Pt Angkasa Pura 1 Di Bandar Udara I Gusti Ngurah Rai Bali - Baiq Husnatul Karunia; Andi Syaputra (Jurnal Mahasiswa: Jurnal Ilmiah Penalaran dan Penelitian Mahasiswa, 2023)
The existence of a retail business at the airport helps meet the needs before, during and after flights. One of the airports that manages its retail business very well, namely I Gusti Ngurah Rai Airport Bali, this is one of the efforts of PT Angkasa Pura I in developing its economy so that it continues to be organized neatly and continues to grow well, this is demonstrated by the establishment of a special unit to manage and operate commercialization in the passenger terminal area, vehicle parking area, and advertising, namely the Commercial Operation Strategic Business Unit. This study aims to determine the attractiveness of passengers to retail business at Ngurah Rai Airport and the quality of retail management at the airport. The research was conducted in the commercial area of ​​the airport. Source of data in this study using secondary and primary data. And for data collection techniques in this study using observation, interviews, and documentation. The results of this study conclude that the attractiveness of passengers to retail business at the airport is the main reason due to personal needs which are then supported by the layout of the room and products, employee service at the outlets, and cleanliness of the outlets. Meanwhile, the quality of retail management is quite good and optimal, namely by planning, supervising, directing by the management, namely Comm.Ops and business partners